Good Governance and Sustainability in Islamic Microfinance Institutions - Kassim, Salina; Hassan, Rusni; Kassim, Siti Nadhirah (IIUM Press, 2018)
In the context of microfinance institutions (MFIs), good governance is highly critical in ensuring that the interests of the diverse stakeholders are being protected, while simultaneously safeguarding the viability and financial sustainability of the institution. As the microfinance industry scales up and expands globally, the decision making and operational processes of the MFIs are becoming increasingly complex, thus the need for stronger governance for the MFIs. This paper explores the relationship between good governance and sustainability particularly in the context of the Islamic MFIs. It also examines the mechanisms of governance in Islamic MFIs by critically evaluating the best practices of governance in the microfinance industry.